Journal of Cellular Immunology 2021
DOI: 10.33696/immunology.3.123
|View full text |Cite
|
Sign up to set email alerts
|

Human Gray and White Matter Metabolomics to Differentiate APOE and Stage Dependent Changes in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia with hallmarks of β-amyloid (Aβ) plaques, tau tangles, and neurodegeneration. Studies have shown that neurodegeneration components, especially brain metabolic deficits, are more predictable for AD severity than Aβ and tau. However, detailed knowledge of the biochemical composition of AD brain tissue vs. normal brain tissue remains unclear. In this study, we performed a metabolomics analysis on the brain tissue of 158 community-based older adults in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(68 reference statements)
4
4
0
Order By: Relevance
“…Accumulating evidence has shown that neurologically and systemically, metabolism may play a more critical role than amyloid beta plaques and tau tangles in AD progression 52 . In line with the findings in the present study, it has been shown that APOE3 and APOE4 carriers develop AD through different metabolic pathways 72 ; therefore, it will be critical for future studies to identify precision nutrition approaches that tailored to different APOE variants to mitigate AD risk. In our prior work, we have demonstrated that inulin reduces neuroinflammatory gene expression and boosts SCFAs production in APOE4 mice, which mitigates their risk for AD development 12 , 13 .…”
Section: Discussionsupporting
confidence: 85%
“…Accumulating evidence has shown that neurologically and systemically, metabolism may play a more critical role than amyloid beta plaques and tau tangles in AD progression 52 . In line with the findings in the present study, it has been shown that APOE3 and APOE4 carriers develop AD through different metabolic pathways 72 ; therefore, it will be critical for future studies to identify precision nutrition approaches that tailored to different APOE variants to mitigate AD risk. In our prior work, we have demonstrated that inulin reduces neuroinflammatory gene expression and boosts SCFAs production in APOE4 mice, which mitigates their risk for AD development 12 , 13 .…”
Section: Discussionsupporting
confidence: 85%
“…It is well documented that TBI increases the risk for developing dementia, such as Alzheimer’s disease (AD) later in life Mortimer et al, 1991 ; Gavett et al, 2010 ; Lee et al, 2013 ; ( Barnes et al, 2016 ). Protecting brain vascular and metabolic functions ( Hammond et al, 2020 ; Hammond et al, 2021 ; Hammond and Lin, 2022 ) is critical to slowing down brain aging ( Hoffman et al, 2017 ) and mitigating the risk for AD ( Lee et al, 2018 ; Lin et al, 2020 ), as these functions serve an essential role in sustaining essential brain activities ( Lin et al, 2008 ; Lin et al, 2010 ). It is also consistent with our previous findings that inulin is protective of systemic metabolism and reduces the risk for AD in a mouse model with human APOE4 alleles, the strongest genetic risk factor for AD ( Hoffman et al, 2019 ; Yanckello et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of our study include the focus on COVID-19 alone. For future work, we plan to extend our work in two directions: first, we will extend the MAE model to handle 3D medical images, such as 3D brain imaging for Alzheimer’s Disease [ 43 , 44 , 45 ]; second, we will explore the potential of the MAE for other tasks, such as image segmentation and localization [ 6 , 46 ], beyond image classification.…”
Section: Discussionmentioning
confidence: 99%